Alcohol consumption and the physical availability of take-away alcohol: Systematic reviews and meta-analyses of the days and hours of sale and outlet density - Sherk, A.; Stockwell, Tim; Chikritzhs, Tanya; Andréasson, S.; Angus, C.; Gripenberg, J.; Holder, H.; Holmes, J.; Mäkelä, P.; Mills, M.; Norström, T.; Ramstedt, M.; et al. (Alcohol Research Documentation, Inc Rutgers, 2018)
Objective: Systematic reviews and meta-analyses were completed studying the effect of changes in the physical availability of take-away alcohol on per capita alcohol consumption. Previous reviews examining this topic have not focused on off-premise outlets where take-away alcohol is sold and have not completed meta-analyses. Method: Systematic reviews were conducted separately for policies affecting the temporal availability (days and hours of sale) and spatial availability (outlet density) of take-away alcohol. Studies were included up to December 2015. Quality criteria were used to select articles that studied the effect of changes in these policies on alcohol consumption with a focus on natural experiments. Random-effects meta-analyses were applied to produce the estimated effect of an additional day of sale on total and beverage-specific consumption. Results: Separate systematic reviews identified seven studies regarding days and hours of sale and four studies regarding density. The majority of articles included in these systematic reviews, for days/hours of sale (7/7) and outlet density (3/4), concluded that restricting the physical availability of take-away alcohol reduces per capita alcohol consumption. Meta-analyses studying the effect of adding one additional day of sale found that this was associated with per capita consumption increases of 3.4% (95% CI [2.7, 4.1]) for total alcohol, 5.3% (95% CI [3.2, 7.4] ) for beer, 2.6% (95% CI [1.8, 3.5]) for wine, and 2.6% (95% CI [2.1, 3.2] ) for spirits. The small number of included studies regarding hours of sale and density precluded meta-analysis. Conclusions: The results of this study suggest that decreasing the physical availability of take-away alcohol will decrease per capita consumption. As decreasing per capita consumption has been shown to reduce alcohol-related harm, restricting the physical availability of take-away alcohol would be expected to result in improvements to public health.